On the Modelling of Road Traffic Crashes: A Case of SARIMA Models - C., Asogwa Oluchukwu; C. M., Eze; C. R., Okonkwo (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2018)
This paper examined the modeling of accident cases in four major roads leading to the main city of Enugu State of Nigeria using SARIMA Models. Among the most robust approaches for analysing time series data is the Autoregressive Integrated Moving Average (ARIMA) model propounded by Box and Jenkins (1979). In this paper, we employed the Box-Jenkins methodology to build SARIMA model for the accident cases for the period, January 2007 to December 2015 with a total of 108 data points. The model obtained in this paper was used to forecast monthly cases of accident in each of the roads for the upcoming year 2016. The forecasted results will help Government and Federal road safety commission to see how to maintain orderliness on the roads to reduce the case of road traffic crashes along the roads